2013
DOI: 10.1016/j.ctim.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Patients with anorexia nervosa receiving acupuncture or acupressure; their view of the therapeutic encounter

Abstract: Study participants perceive the therapeutic relationship and empathy as important qualities of the acupuncture or acupressure intervention as an adjunct therapy for the treatment of anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
2
17
0
2
Order By: Relevance
“…Research into acupuncture and AN shows that there may be some benefit from acupuncture as an adjunct treatment, not as a primary source of treatment for AN. 9,11,13 An understanding of the benefits of treatment needs to be communicated clearly when discussing treatment aims and expectations with no false hope of cure. 1 Specific to an outpatient or clinic setting:…”
Section: Effective Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into acupuncture and AN shows that there may be some benefit from acupuncture as an adjunct treatment, not as a primary source of treatment for AN. 9,11,13 An understanding of the benefits of treatment needs to be communicated clearly when discussing treatment aims and expectations with no false hope of cure. 1 Specific to an outpatient or clinic setting:…”
Section: Effective Communicationmentioning
confidence: 99%
“…The therapeutic relationship is very important to AN patients' recovery, [13][14][15][16] however the development of the therapeutic relationship can be difficult and this may be more challenging in settings where there are disagreements, power struggles or competing goals of care and therapy. 14,15,17 It has been shown that non-familial relationships (with a partner or a therapist) play a major role in recovery for AN patients.…”
Section: Professional Traits and Qualities Of The Practitioner An Trementioning
confidence: 99%
See 1 more Smart Citation
“…While there are a number of theoretical research papers/theses investigating the use of acupuncture for the treatment of ED's [21][22][23][24][25], there is little information about the practical/clinical presentation of the ED sufferer seeking acupuncture treatment [25,26]. Utilising the collective cases of acupuncturists, experienced in treating those with ED's, may provide a better understanding of how ED's present in TCM practice and how they are treated which may, in turn, inform clinicians and guide further research questions.…”
Section: Bulimia Nervosamentioning
confidence: 99%
“…-This population can benefit from a therapist who understands ED's and some of the issues patients are going through. The therapeutic relationship is a very important aspect of the acupuncture consultation, and the cultivation of the therapeutic relationship is central to successful treatment [24]. -Safety at the clinic is very important; it needs to be a safe place for the eating disordered patient to attend.…”
Section: Clinical Observationsmentioning
confidence: 99%